Human–AI Collaboration in Tourism Work: A Systematic Review of Impacts on Jobs and Skills - Ika Anggari, Baiq Yolanda (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
This study presents a systematic literature review (SLR) of artificial intelligence (AI) and its implications for employment, skills, and human–AI collaboration in the tourism and hospitality industry. AI technologies such as chatbots, service robots, biometric systems, and predictive analytics are increasingly adopted to improve efficiency and service delivery, but their impacts on workers remain contested. Using the PRISMA protocol, 97 peer-reviewed articles published between 2010 and 2024 were analyzed from Scopus, Web of Science, and ScienceDirect. The review reveals three central themes. First, AI is automating repetitive tasks in areas such as check-in, information provision, and reservations, leading to concerns about job displacement. Second, new opportunities are emerging as AI creates demand for advanced digital, analytical, and problem-solving skills, suggesting a gradual shift in workforce requirements. Third, human–AI collaboration is developing as a hybrid model, where workers complement AI technologies by providing emotional intelligence, cultural sensitivity, and personalized interactions that machines cannot replicate. Challenges include skill mismatches, worker resistance, ethical concerns, and uneven adoption across regions and enterprise scales. The findings emphasize that AI should be understood not as a substitute for human labor but as a transformative force reshaping workforce structures, necessitating strategies for reskilling and sustainable collaboration.